A big data prediction framework for weather forecast using MapReduce algorithm - Khalid, Adam; Mazlina, Abdul Majid; Fakherldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain (Publishing Technology, 2017)
Weather forecasting plays a vital role in daily routine, businesses and their decisions. The process of weather forecasting is developing as the effect of advancement in technology right from the realization of increasing size of data, Weather forecasting was found to be based on big data. The researchers have taken review with the objective to study the current forecasting process and methods, and the need of a data structure is recognized for handling the weather data, which is bigger in size, used for the process of weather forecasting. This paper presents a big data analysis framework for weather dataset based on MapReduce Algorithm, and offers not only weather dataset analysis, but also various analytic capabilities on huge amounts of data. However, this work establishes a guideline for researchers and industrial practitioners on how to analysis big data.